Mental illness action taken in workplace - Ismail, Fadillah; Daman Huri, Mohammad Hasrul; Abdul Kadir, Adibah; Salim, Siti Aisyah (Penerbit UTHM, 2020)
It is approximately 450 million people have been analysed with mental illness around the world, where mental illness, substance abuse and neurological diseases contribute to 13% of the worldwide disease burden. The World Health Organization (WHO) gauge that 1 in 4 individuals experience mental illness at a few points in their life. That means almost 25% of the population has a mental illness. According to Datuk Seri Dr. S. Subramaniam Depression, on normal, accounts for 4.3% of the by and large burden of cobalt disease, which is one of the biggest causes of morbidity. Mental illness or also been called as mental health disorders, it is a wide scope of emotional well-being problem of scatters that impact your personality, considering and conduct. Tension issue, dietary issues, addictive practices, discouragement and schizophrenia which are the instances of dysfunctional behaviour.